Systematic review of 2008-2012 literature and update of recommendations for the use of methotrexate in rheumatic diseases, with a focus on rheumatoid arthritis - M. Todoerti; W. Maglione; E. Bernero; A. Bortoluzzi; M. Colaci; E. Galuppi; S. Paolino; R. Talarico; M. Cutolo; C. Ferri; F. Trotta; S. Bombardieri; et al. (PAGEPress Publications, 2013)
The objective of this review is to update the recommendations of the 2010 Italian Consensus on the use of methotrexate (MTX) in rheumatoid arthritis (RA) and other rheumatic diseases. The literature published between 2008 and 2012 was systematically reviewed and updated recommendations on MTX use in rheumatic diseases, particularly RA, were formulated. These recommendations were approved by a panel of expert Italian Rheumatologists. A total of 10,238 references were identified, among which 70 studies were selected for critical evaluation. Sufficient evidence had accumulated to warrant changes to several of the recommendations in the new version. A new recommendation for patients with RA who are in MTX-induced clinical remission was also proposed and approved by the panel. Updated recommendations for the use of MTX in patients with RA or other rheumatologic disease are proposed.